2020
DOI: 10.1007/s00148-020-00773-7
|View full text |Cite
|
Sign up to set email alerts
|

The sex ratio and global sodomy law reform in the post-WWII era

Abstract: This paper studies the role of population sex ratio, i.e. ratio of men to women, in the global wave of sodomy law reform in the post-WWII era. Using a global survey, this paper first finds that men are more homophobic than women and such pattern has persisted across countries and time. With a newly constructed panel data of 183 countries, this paper then finds that high sex ratio causally makes sodomy law less likely to be repealed. The result is robust to numerous checks, including using temperature as an ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…3 Moreover, there are a few studies specifically looking at sodomy laws that are closely related to our research question. For instance, Chang (2021) found that countries with high malefemale sex ratios were less likely to decriminalize same-sex sexual activities, possible due to the fact that men are on average less tolerant than women with regards to homosexuality. Kenny and Patel (2017)-as well as Asal, Sommer, and Harwood (2013)-emphasized instead the role played by legal institutions: that is, the higher probability of having sodomy laws in countries that were formerly part of the British Empire.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Moreover, there are a few studies specifically looking at sodomy laws that are closely related to our research question. For instance, Chang (2021) found that countries with high malefemale sex ratios were less likely to decriminalize same-sex sexual activities, possible due to the fact that men are on average less tolerant than women with regards to homosexuality. Kenny and Patel (2017)-as well as Asal, Sommer, and Harwood (2013)-emphasized instead the role played by legal institutions: that is, the higher probability of having sodomy laws in countries that were formerly part of the British Empire.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By doing so, this article extends an extremely limited literature on sodomy laws not only in economics and political science but also in public health and other social sciences. A few studies have looked at the determinants of sodomy laws (Frank, Camp, and Boutcher 2010;Asal, Sommer, and Harwood 2013;Chang 2021) or at the effect of legalizing homosexuality across countries on attitudes toward sexual minorities (Kenny and Patel 2017). Yet, to the best of our knowledge, there is no study specifically looking at the impact of sodomy laws on crime or arrest rates.…”
Section: Introductionmentioning
confidence: 99%
“… 10 At an aggregate level, countries with English common law, a communist past, or high (contemporary) sex ratios are less accepting of homosexuality (Asal et al, 2013 ; Andersen & Fetner, 2008 ; Chang, 2021 ) These studies do not address the potential endogeneity of such cross-country differences. Aksoy et al ( 2020 ) exploit the gradual rollout of same-sex relationship recognition throughout Europe to demonstrate how laws can shape attitudes towards sexual minorities.…”
mentioning
confidence: 99%
“…The global importance of the topic is also demonstrated by the fact that almost 2.7bn people are living in countries where identifying as a sexual orientation or gender identity minority could lead to imprisonment, corporal punishment or even death (Drydakis, 2017a). Chang (2020) has investigated the evolution of the legal situation of sexual orientation across countries after the Second World War and examined global causes. Further research efforts may help to provide a better understanding and to foster societal changes.…”
mentioning
confidence: 99%